2022
DOI: 10.3389/fimmu.2022.992060
|View full text |Cite
|
Sign up to set email alerts
|

An antigen processing and presentation signature for prognostic evaluation and immunotherapy selection in advanced gastric cancer

Abstract: ObjectiveThe aim of the study was to propose a signature based on genes associated with antigen processing and presentation (APscore) to predict prognosis and response to immune checkpoint inhibitors (ICIs) in advanced gastric cancer (aGC).BackgroundHow antigen presentation-related genes affected the immunotherapy response and whether they could predict the clinical outcomes of the immune checkpoint inhibitor (ICI) in aGC remain largely unknown.MethodsIn this study, an aGC cohort (Kim cohort, RNAseq, N=45) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…On the contrary, closer interactions between neutrophils and Th1 cells and CTL through B2M-CD3D and B2M-KLRD1 pairs, involving in the AP pathway were observed in the tumour-free TDLN (Figure S9B and C). 57 The NicheNet method showed that, with neutrophils as signal transmitters in the tumour-invaded TDLNs, CCL3/CCL4-CCR1 pairs were also dominant in mediating the interactions between neutrophils and macrophages, consistent with the findings of CellChat analysis (Figures S9D and F). Furthermore, the target genes of neutrophils-macrophages/endothelial cells interactions were correlated with angiogenesis (e.g., VEGFA, VCAM1 and MMP14) and epithelial-mesenchymal transition (e.g., PDGFD, CXCL12 and IGF1) processes (Figures S9E and 9G).…”
Section: Neutrophils Showed Intimate Interplay With Th1 Cells and Mac...supporting
confidence: 81%
See 1 more Smart Citation
“…On the contrary, closer interactions between neutrophils and Th1 cells and CTL through B2M-CD3D and B2M-KLRD1 pairs, involving in the AP pathway were observed in the tumour-free TDLN (Figure S9B and C). 57 The NicheNet method showed that, with neutrophils as signal transmitters in the tumour-invaded TDLNs, CCL3/CCL4-CCR1 pairs were also dominant in mediating the interactions between neutrophils and macrophages, consistent with the findings of CellChat analysis (Figures S9D and F). Furthermore, the target genes of neutrophils-macrophages/endothelial cells interactions were correlated with angiogenesis (e.g., VEGFA, VCAM1 and MMP14) and epithelial-mesenchymal transition (e.g., PDGFD, CXCL12 and IGF1) processes (Figures S9E and 9G).…”
Section: Neutrophils Showed Intimate Interplay With Th1 Cells and Mac...supporting
confidence: 81%
“…On the contrary, closer interactions between neutrophils and Th1 cells and CTL through B2M–CD3D and B2M–KLRD1 pairs, involving in the AP pathway were observed in the tumour‐free TDLN (Figure S9B and C ). 57 …”
Section: Resultsmentioning
confidence: 99%
“…Shi et al proposed a Gluco-Immune Score by analyzing the TME where gastric cancer (GC) patients with high scores are beneficiaries of IT [ 21 ] as well as the use of a gene-based antigen processing and presentation signature (APscore) suggested by Wang et al [ 22 ]. The importance of TME in affecting responses to ICI were also underlined by Zeng at al.…”
Section: Dissecting the Tme With Multi-omics Approachmentioning
confidence: 99%
“…This mechanism allows cancer cells to evade the immune system and continue to proliferate. Strategies focused on enhancing antigen presentation may help reactivate anti-tumor immunity 163 . Presenting new neoantigens, which are unique to individual tumors, is another potential approach to improve the efficacy of gastric cancer treatment 163 .…”
Section: Future Outlook: Biomarker Research Directionsmentioning
confidence: 99%